Plasmonic Filters Based on Lithographically Patterned and Hexagonally Arranged Triangular Silver Nanoparticles Array. (5th July 2015) - Liu, Jing; Cai, Haoyuan; Tang, Kai; Kong, Lingqi
Abstract : A plasmonic filter applied in visible regime is proposed on the basis of hexagonally arranged triangular silver nanoparticle arrays. A method using discrete dipole approximation (DDA) to aid design parameters of the silver nanoparticle arrays is adopted for the filter design and optimization on the basis of computational numerical calculation. The influence of the particle's thickness and period on the extinction spectrum is studied using the DDA-based computational analysis. Considering the nanofabrication condition, arrays with 40 nm thickness and 230 nm period are selected and fabricated by using nanosphere lithography (NSL) technique. The experimental spectrum is basically in agreement with the theoretical spectrum derived by the DDA calculation.